Clinical Characteristics of Endometrial Stromal Sarcoma From an Academic Medical Hospital in China. Issue 9 (1st November 2010) - Jin, Ying; Pan, Lingya; Wang, Xueqing; Dai, Zhiqin; Huang, Huifang; Guo, Lina; Shen, Keng; Lian, Lijuan
Abstract : Objectives: The purpose of this study was to evaluate the clinical features, treatments, and outcomes of endometrial stromal sarcoma (ESS) in China. Methods: Seventy consecutive ESS patients were treated at Peking Union Medical College Hospital from 1983 to 2005, and 51 of them completed the treatment and follow-up. The demographic, clinicopathologic, treatment, and survival information was retrospectively reviewed. Data were analyzed using Kaplan-Meier methods and Cox proportional hazards regression. Results: In all, the mean age of the patients was 43.5 years. Irregular vaginal bleeding and uterine enlargement were presented in 71.0% and 65.7% of the cases, respectively. Uterine cavity lesions were found in 17 patients (24.3%). Twenty-six cases (37.2%) were diagnosed preoperatively through diagnostic curettage. Among 51 patients who completed the treatment and follow-up in Peking Union Medical College Hospital, 37 were diagnosed as having low-grade ESS (LGESS) and 14 high-grade ESS, which is now classified as undifferentiated endometrial sarcoma (UES). The median overall survival time was 334 months, and the 5-year survival rate was 87.8%. Twenty-six of 51 patients, including 14 with LGESS and 12 with UES, developed disease recurrence. The tumor's classification, initial surgery, and adjuvant therapy were the factors related to the disease-free survival, whereas only the tumor's classification was associated with the overall survival. Conclusions: Endometrial stromal sarcoma is a rare kind of uterine malignancy; the possibilities of preoperative diagnosis may be improved by diagnostic curettage. Low-grade ESS and UES represent 2 distinct clinical entities and should be treated as such. The tumor's classification may be the most important prognostic factor.